Hyperkalemic cardiac arrest induced by mannitol administration during craniotomy: A case report and review of the literature - Zheng, Hua; Cao, Xueqin; Gao, Feng; Li, Xinhua; Wan, Li; Luo, Ailin (Frontiers in Surgery, 2022)
Introduction: Mannitol is the most widely used hyperosmolar agents during neurosurgical procedures. However, its use can lead to serious hyperkalemia with altered cardiac conduction. Case presentation: Here we report a case in which a 40-min cardiac arrest was caused by mannitol-induced hyperkalemia during craniotomy. In addition, we conducted a literature review through a PubMed (MEDLINE) search of the relevant literature published so far. Details of all cases are presented and discussed. The results suggest that male patients or patients with uncontrolled diabetes might be at higher risk to develop this phenomenon. The results also suggest that the high dose and rapid rate of infusion of mannitol might contribute to mannitol-induced hyperkalemia. Conclusion: Physicians should be aware the existence of mannitol-induced hyperkalemia. Although the mechanism of this complication is not well established, it is prudent to administer mannitol cautiously, especially in patients with uncontrolled diabetes. Continuous electrocardiogram monitoring and frequent measurements of serum electrolytes can help to detect and treat possible life-threatening events induced by mannitol-induced hyperkalemia early.